Autopoiesis in organization theory and practice - Magalhaes, Rodrigo, 1950-; Sanchez, Ron. (Bingley, U.K. : Emerald, 2009)
'Autopoiesis in Organization Theory and Practice' considers the potential of autopoiesis theory to provide a new unifying framework for the study of organizations as systems and of organizational phenomena as emergent phenomena. The papers in this volume integrate open systems theory with the pioneering work of Maturana and Varela (1980, 1992) on autopoiesis in biological systems. Viewing organizations as living systems opens a powerful new perspective for describing, explaining, and even predicting organizational phenomena across the full spectrum of organizations and environments, from stable to highly dynamic. This collection of papers brings into focus both the great potential and the important challenges facing organizational thinkers in building new organization theory and deriving new principles for management practice based on autopoiesis theory. Topics include the fundamental features of autopoiesis theory, the key conceptual issues surrounding the use of autopoiesis concepts in representing and analyzing organizations as living systems, and the practical applications of autopoiesis theory in designing organizations and managing organizational processes.
ch. 1. Autopoiesis theory and organization : an overview / Rodrigo Magalh{u4865}s, Ron Sanchez -- ch. 2. Outlining the terrain of autopoietic theory / John Brocklesby -- ch. 3. Overcoming autopoiesis : an enactive detour on the way from life to society / Ezequiel A. Di Paolo -- ch. 4. Innovation and organization : an overview from the perspective of Luhmann's autopoiesis / Tore Bakken, Tor Hernes, Eric Wiik -- ch. 5. Autopoiesis and organizations : a biological view of social system change and methods for their study / Chris Goldspink, Robert Kay -- ch. 6. Autopoiesis and critical social systems thoery / Christian Fuchs, Wolfgang Hofkirchner -- ch. 7. Productive misunderstandings between organization science and organization practice : the science-practice relation from the perspective of Niklas Luhmann's theory of autopoietic systems / David Seidl -- ch. 8. Plugging the theoretical gaps : how autopoietic theory can contribute to process-based organizational research / John Brocklesby -- ch. 9. An autopoietic understanding of'innovative organization' / Tore Bakken, Tor Hernes, Eric Wiik -- ch. 10. Information in organizations : rethinking the autopoietic account / Ian Beeson -- ch. 11. Autopoiesis and the evolution of information systems / Marleen Huysman, Heico van der Blonk, Edu Spoor -- ch. 12. The autopoiesis of organizational knowledge, learning, and memory / Steffen Blaschke -- ch. 13. Autopoiesis : building a bridge between knowledge management and complexity / Robert Kay, Chris Goldspink -- ch. 14. Autopoiesis as the foundation for knowledge management / Paul Parboteeah, Thomas W. Jackson, Gillian Ragsdell -- ch. 15. Autonomous cooperation : a way to implement autopoietic characteristics into complex adaptive logistic systems? / Michael H$1#7H(Bsmann, Bernd Scholz-Reiter, Philip Cordes, Linda Austerschulte, Christoph de Beer, Christine Wycisk -- ch. 16. The autopoiesis of decisions in school organizations : conditions and consequences / Raf Vanderstraeten.s
Keywords: Organizational sociology; Autopoiesis